Affective assessment in learning using fuzzy logic / Lusiana Syaiful - Syaiful, Lusiana (2016)
Affective assessment is getting attention in education as it relates towards students' emotion in learning. Studies also showed that emotions play a vital role for students during learning sessions. Currently, there is no specific mechanism to access the affective value during the computer based learning environment. This research presents the work done in order to assess the affective value of the learner during computer-based learning. Using questionnaire of personal preferences was found feasible to be used in recognizing emotion. A framework for developing fuzzy logic in measuring emotion was proposed. An affective assessment with Object Oriented Programming subject was developed as the test instrument for the framework. Participants were required to answer set of assessment with preference questions. The actual result from the research is then compared with expected result of emotions from participant to test the accuracy. The results then produce the state of emotions and its percentage. Based on the results, it is recommended that the framework to be used in measuring emotions implement Fuzzy Logic with Fuzzy Expert System techniques.